Strategi Pemasaran Pantai Dream Island Di Mertasari Desa Intaran Sanur Kauh Kota Denpasar - Samosir, Laura Therecia; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 8 No 2 (2020): VOL 8, NO 2 (2020): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2020.v08.i02.p04, 2020)
Tourism in Indonesia has recently grown rapidly in one of them in the city of Bali. Bali has a very beautiful natural potential, one of the natural potentials developed is coastal tourism. Dream Island Mertasari Sanur Beach is one of the beaches that is still new but has a lot of potentials. Therefore, this study was conducted to determine the existing conditions and marketing strategies that exist on Dream Island the Mertasari Beach Sanur Kauh City of Denpasar. The method used in this study is a qualitative descriptive method with data sources in the form of primary data and secondary data. The primary data in this study are data sourced from direct observation to the location of the study and by interviewing informants. While secondary data in this study are data obtained from documentation and literature to complete the primary data. The technique of determining the informants used was purposive sampling. The results showed that the existing conditions on Dream Island Beach based on Concept 4a were still lacking. The condition of the attraction is very good but for access and facilities still, have some disadvantages that need to be improved in the future. The reality that is on Dream Island Beach only consists of private parties and village institutions. The marketing strategy at Dream Island Beach has not been optimal due to several problems such as business license constraints and lack of cooperation with promotional media.   Keywords:  Marketing Strategic, attraction, Dream Island Beach